Clinical Spectrum and Outcome of Childhood IgA Nephropathy - A Single Centre Experience - Rumana, Jubaida; Iyengar, Arpana; Vasudevan, Anil (Northern International Medical College Journal, 2015)
Background : IgA nephropathy (IgA N) is one of the most common primary glomerulonephritis worldwide. Although there is paucity of data on the clinical spectrum and outcome of childhood IgA nephropathy in India as well as South Asia. Objective : The aim of this retrospective study was to describe the clinical spectrum, histological findings, and outcome of the children with IgA nephropathy. Methods : This retrospective study was conducted at Peadiatric Nephrology Department of St Johns medical college Hospital, Bangalore India. Fifteen children with histopathologically proven diagnosis of IgA N between 2010 to 2013 were included for analysis. The baseline demographics, along with clinical data, laboratory and renal biopsy details at the time of presentation and during follow up were retrieved from patient case records. Renal biopsy was classified based on Hass classification. All patients with class III and IV received immunosuppressive therapy while the rest received ACE inhibitors or no specific therapy. Results : Among the 15 patients with IgA N, male to female ratio was 1:2 .The average age at presentation was 10 years (range 4½ years to 15 years) and the median follow up was 9 months (Inter Quartile range- 21 months). The most common clinical presentation was nephritic features with nephrotic range proteinuria (60%) followed by isolated gross hematuria (20%). The age at presentation was not associated with a specific clinical presentation. Ten patients had abnormal Estimated Glomerular Filtration Rate (eGFR) at the time of presentation. The renal biopsy revealed class III in 3 patients, class IV in 3 patients and class V in 3 patients. There was no correlation between histopathology and clinical presentation. Class I which was most common histopathology type (seen in 40% of biopsies) was associated with various clinical presentations. At the last follow up 53% and 27% children were in complete and partial remission respectively, also 20% children progressed to Chronic Kidney Disease (CKD). Conclusion : In this study of children with IgA N, the most common presentation was nephritic features with nephrotic range proteinuria and the most common histopathology feature was Class I. IgA N is associated with significant morbidity as 27 % of children at last follow up were in partial remission or 20 % progressed to CKD. Northern International Medical College Journal Vol.7(1) Jul 2015: 97-100